2002
DOI: 10.3354/meps242215
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of larval rockfishes Sebastes spp. across nearshore fronts in a coastal upwelling region

Abstract: We sampled larval fishes along cross-shelf transects off Granite Canyon, California, USA, during the upwelling seasons of 1993 and 1994 to determine whether coastal upwelling fronts affect the cross-shelf distribution of larval rockfishes Sebastes spp. during the earliest period of planktonic life. Rockfish larvae occurred in relatively high densities near surface fronts and were distributed in patches oriented along sloping pycnoclines contiguous with surface fronts. Qualitative comparisons between observed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 53 publications
(68 reference statements)
2
53
0
2
Order By: Relevance
“…Fronts are associated with phytoplankton blooms and aggregate phytoplankton and larvae, and these phenomena are well-documented in central California (Bjorkstedt et al, 2002;Graham et al, 1992;Ryan et al, 2010Ryan et al, , 2014Traganza and Conrad, 1981;Woodson et al, 2009). Fronts are common and persistent in the CCS (Castelao et al, 2006;Shanks et al, 2003a), and are spatially correlated with higher recruitment of both intertidal and subtidal species .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fronts are associated with phytoplankton blooms and aggregate phytoplankton and larvae, and these phenomena are well-documented in central California (Bjorkstedt et al, 2002;Graham et al, 1992;Ryan et al, 2010Ryan et al, , 2014Traganza and Conrad, 1981;Woodson et al, 2009). Fronts are common and persistent in the CCS (Castelao et al, 2006;Shanks et al, 2003a), and are spatially correlated with higher recruitment of both intertidal and subtidal species .…”
Section: Discussionmentioning
confidence: 99%
“…Highly variable in space and time, ocean currents have unpredictable effects on transport (Mitarai et al, 2008), especially over shorter, non-seasonal timescales. For example, larvae can be entrained in seaward-growing filaments (Bjorkstedt et al, 2002;Strub et al, 1991) or otherwise transported offshore, but they also can be entrained in transiently stationary eddies or fronts that may result in little net transport (Fig. 1), at least temporarily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have found higher densities of larval rockfishes associated with upwelling fronts in central California (Larson et al, 1994;Sakuma and Ralston, 1995;Bjorkstedt et al, 2002), indicating that upwelling conditions play an integral role in the transport and delivery of larval fishes. For instance, years of above average onshore transport of surface waters in the California current eco system resulted in successful widow rockfish (Sebastes entomelas) recruitment classes (Norton, 1987), while strong upwelling during the winter months resulted in low overall juvenile rockfish abun dance as examined in seabird diets (Ainley et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Equatorward wind stress displaces coastal surface waters offshore via Ekman transport, which are replaced by colder, nutrient rich, subsurface waters (Huyer, 1983). Because of their relatively limited locomotory abilities, planktonic larvae may become entrained in the surface Ekman layer and accumulate in offshore coastal fronts (Bjorkstedt et al, 2002). These coastal fronts interact with alongshore current systems, and provide a means for larval dispersal to connect distant populations.…”
Section: Introductionmentioning
confidence: 99%